Renin–angiotensin system inhibitors reduce cardiovascular mortality in hypertensive patients with severe aortic stenosis undergoing transcatheter aortic valve implantation: insights from the EffecTAVI registry - Basile, Christian; Mancusi, Costantino; Franzone, Anna; Avvedimento, Marisa; Bardi, Luca; Angellotti, Domenico; Castiello, Domenico Simone; Mariani, Andrea; Manzo, Rachele; De Luca, Nicola; Cirillo, Plinio; De Simone, Giovanni; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Arterial hypertension is associated with renin–angiotensin system triggering, leading to left ventricle fibrosis and worse cardiovascular outcomes. Patients with comorbid arterial hypertension and severe aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI) in the EffecTAVI registry were selected to evaluate the impact of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) on cardiovascular mortality. Methods: We enrolled 327 patients undergoing TAVI from the EffecTAVI registry. Using Kaplan–Meier event rates and study-stratified multivariable Cox proportional hazards regression models, we evaluated 2 years clinical outcomes according to ACEIs/ARBs therapy status at the enrollment. Results: Among the included patients, 222 (67.9%) were on ACEIs/ARBs at baseline, whereas 105 (32.1%) were not. Treatment with ACEIs/ARBs was significantly associated with decreased 2 years cardiovascular mortality (HR=0.44, 95% CI 0.23-0.81, p=0.009). This association remained stable after both multivariable adjustment and propensity score matching. Conclusion: In a cohort of hypertensive patients with severe AS from the EffecTAVI registry, ACEIs/ARBs treatment at baseline was independently associated with a lower risk of 2-year cardiovascular mortality, suggesting a potential benefit of this treatment, therefore further trials are needed.